SmartORC: smart orchestration of resources in the compute continuum - Carlini, Emanuele; Coppola, Massimo; Dazzi, Patrizio; Ferrucci, Luca; Kavalionak, Hanna; Korontanis, Ioannis; Mordacchini, Matteo; Tserpes, Konstantinos (Frontiers in High Performance Computing, 2023)
The promise of the compute continuum is to present applications with a flexible and transparent view of the resources in the IoT-Edge-Cloud ecosystem. However, such a promise requires tackling complex challenges to maximize the benefits of both the cloud and the edge. Challenges include managing a highly distributed platform, matching services and resources, harnessing resource heterogeneity, and adapting the deployment of services to the changes in resources and applications. In this paper, we present SMARTORC, a comprehensive set of components designed to provide a complete framework for managing resources and applications in the Compute Continuum. Along with the description of all the SMARTORC subcomponents, we also provide the results of an evaluation aimed at showcasing the framework's capability.